2011
DOI: 10.1186/1476-511x-10-150
|View full text |Cite
|
Sign up to set email alerts
|

Phytoceramide and sphingoid bases derived from brewer's yeast Saccharomyces pastorianus activate peroxisome proliferator-activated receptors

Abstract: BackgroundPeroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that regulate lipid and glucose metabolism. PPARα is highly expressed in the liver and controls genes involved in lipid catabolism. We previously reported that synthetic sphingolipid analogs, part of which contains shorter-length fatty acid chains than natural sphingolipids, stimulated the transcriptional activities of PPARs. Sphingosine and dihydrosphingosine (DHS) are abundant sphingoid bases, and ceramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Our results therefore indicate that PHS and phCer in traditional Japanese fermented food might help to prevent the development of type 2 diabetes. 4) We have recently reported that 4,8-sphingadienine enhanced ceramide production in the skin by activating PPARs. 16) Since many other subclasses of sphingolipid are present in food, we should determine in a future study which type of sphingolipid is important in daily food.…”
Section: Improved High-fat Diet-induced Glucose Intolerance By An Oramentioning
confidence: 99%
See 3 more Smart Citations
“…Our results therefore indicate that PHS and phCer in traditional Japanese fermented food might help to prevent the development of type 2 diabetes. 4) We have recently reported that 4,8-sphingadienine enhanced ceramide production in the skin by activating PPARs. 16) Since many other subclasses of sphingolipid are present in food, we should determine in a future study which type of sphingolipid is important in daily food.…”
Section: Improved High-fat Diet-induced Glucose Intolerance By An Oramentioning
confidence: 99%
“…4) PHS and phCer are the major sphingolipids in yeast and fungi, and are thus present in the fermented food consumed almost exclusively by the Japanese. Our results therefore indicate that PHS and phCer in traditional Japanese fermented food might help to prevent the development of type 2 diabetes.…”
Section: Improved High-fat Diet-induced Glucose Intolerance By An Oramentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that peroxisome proliferator-activated receptor PPAR agonists promote keratinocyte differentiation 32 . These PPARs can be activated by sphingoid bases 9,37,38 . According to Shirakura et al 9 , the activation of PPARγ requires a double bond at the C8 position of sphingoid bases.…”
Section: Discussionmentioning
confidence: 99%